Runoff Variation and Influencing Factors in the Kuye River Basin of the Middle Yellow River - He, Yi; Mu, Xingmin; Jiang, Xiaohui; Song, Jinxi (Frontiers in Environmental Science, 2022)
In recent decades, due to climate change and human activities, the hydrological processes of many rivers in the world have undergone significant changes. As an important part of the water cycle, it is of great practical significance to identify the causes of runoff change for water resource management and planning. Taking the Kuye River and its tributaries, the Wulanmulun River and Beiniuchuan River as examples, the trend change in runoff was investigated by the Mann-Kendall trend test and mutation analysis, and the contribution of influencing factors of runoff change was quantitatively evaluated by the Budyko framework. The results showed that the annual runoff depth of the Kuye River basin and its tributaries, the Wulanmulun River basin and Beiniuchuan River basin, showed a significant decreasing trend from 1960 to 2014 (P<0.01), and the decreasing rates were 1.03 mm/a, 1.24 mm/a and 1.50 mm/a, respectively. The abrupt change point of runoff depth in the Kuye River basin and its upstream Beiniuchuan River basin occurred in 1996, while that in the Wulanmulun River basin, another tributary, occurred in 1992. In the Kuye River basin, Beiniuchuan River basin and Wulanmulun River basin, the contributions of underlying surface change to runoff change were 89.03%, 89.54% and 95.42%, respectively, followed by the contribution of rainfall, and the contribution of potential evapotranspiration to runoff change was the lowest. The change in the underlying surface (the Grain for Green Project and coal mining) is the main factor causing the decrease in runoff in the Kuye River basin.